The role of women: gender equality for sustainable development - Zilli, Sandro (Community Notebook. People, Education and Welfare in the Society 5.0, 2022)
Gender equality is not a mathematical issue, it is first and foremost a value principle based on the possibility of equal treatment of men and women in order to have free access to certain functions and roles within society. It is in fact a cultural and organisational revolution in which women are the protagonists. Why women? Because the income disparity in the same job positions is still great, their career advancement is often restricted, and top or managerial roles are still de facto reserved for men. Not to mention the fact that they have more difficulty in finding work because motherhood is seen as an obstacle.